Implications of Service and Product Attributes on Customer Loyalty - Haris, Abdul (Advances: Jurnal Ekonomi & Bisnis, 2023)
Purpose: This study aims to examine (1) the effect of service quality on customer loyalty, (2) the effect of product attributes on customer loyalty, and (3) to determine whether service quality or product attributes have a more dominant influence on customer loyalty at KFC Pengayoman in Makassar. Research Design and Methodology: The study employs a field research method, with primary data collected directly from KFC Pengayoman customers in Makassar. Data collection techniques include observation, questionnaires, and literature reviews. Respondents were customers who purchased products from KFC Pengayoman, and secondary data was gathered through relevant documents to complement the primary data. Findings and Discussion: The results showed that service quality has a significant effect and is the dominant factor in customer loyalty, while product attributes have no significant impact. This finding emphasizes the importance of maintaining service quality to increase customer loyalty, especially in the fast food industry. Implications: The findings suggest that managers should prioritize improving service quality while continuously innovating product attributes to meet customer expectations and remain competitive. A strong focus on service excellence will enhance customer retention and brand strength in a competitive market.